2014
DOI: 10.1021/jf500901a
|View full text |Cite
|
Sign up to set email alerts
|

Factors Limiting the Enzymatic Hydrolysis of Wheat Gluten

Abstract: The enzymatic hydrolysis of wheat gluten for the production of seasonings using mixtures of endo- and exopeptidases results in yields typically below 40%. Possible limiting parameters, such as an increasing product inhibition, autopeptidolysis of the enzymes, and lack of cleavage sites, were studied using novel peptidases from Flammulina velutipes or the commercial Flavourzyme preparation. Seven intermittent electrodialysis steps (10 g/L gluten and 10 kaU/mL) for the in situ removal of amino acids minimized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…As illustrated in figure 11 d , the surface of the cuticle was improved to be flat but a little acute at the edge, which means WPH had some effect to recover the damaged hair. The result is in agreement with Vila's [ 10 ] result that protein hydrolysate would contribute to the sealing of the cuticles. Figure 11 e is the SEM image of the dry hair treated with QWPH shampoo, where the surface morphology of hair is flat, smooth with a little fracture.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As illustrated in figure 11 d , the surface of the cuticle was improved to be flat but a little acute at the edge, which means WPH had some effect to recover the damaged hair. The result is in agreement with Vila's [ 10 ] result that protein hydrolysate would contribute to the sealing of the cuticles. Figure 11 e is the SEM image of the dry hair treated with QWPH shampoo, where the surface morphology of hair is flat, smooth with a little fracture.…”
Section: Resultssupporting
confidence: 92%
“…For the past decades, lots of methods including physical, chemical and enzymatic methods have been used to modify wheat gluten [8][9][10][11], and many types of protein hydrolysate from plants and animals have been used in hair repair products [6,12]. However, few were focused on the disassociation behaviour of protein hydrolysate in hair care products which is not suitable for adherence.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the bands of gliadins became weak after hydrolysis with alcalase and papain (Figure 2A, lanes 3 and 4), indicating that a part of the gliadins was hydrolyzed into small peptides. 28 The amount of disulfide bonds (SS) was found to be another structural factor of gluten that is closely related to its allergenicity. The result showed that phosphorylation and alcalase and papain hydrolysis increased the SH content significantly in comparison to the raw gliadins (Figure 2B).…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…This is confirmed in previous studies of wheat gluten hydrolysis using Flavourzyme Ò . A combined effect of product inhibition and lack of cleavage sites produced SDS-PAGE bands around 30 kDa (Grimrath et al, 2011;Giesler et al, 2014).…”
Section: Resultsmentioning
confidence: 99%